Peripheral vascular access as exclusive access mode in pediatric intensive care unit - Armstrong, Sonya Hayes; Gangu, Shantaveer; West, Alina Nico; Spentzas, Thomas (Frontiers in Pediatrics, 2023)
INTRODUCTION: The type (central or peripheral) of vascular access in pediatric critical care depends on how long the treatment is needed, the properties of the medication (osmolarity or vesicant), and the need for central pressure monitoring. An increasing number of patients are managed by peripheral intravascular catheters (PIVCs). Extended dwell or midline catheters are another peripheral access option besides PIVCs, but currently, there are no recommendations for their placement. OBJECTIVES: The goal is to estimate the dwell time of PIVCs, analyze the specific parameters affecting it, and develop recommendations for switching to extended dwell and midline catheter placement when peripheral access is preferred. METHODS: The study enrolled patients aged 0-18 admitted to PICU for over 24 hours and managed with peripheral access only over two years (2019-2021). RESULTS: Four hundred eighty-four patients fulfilled the criteria. Patients with peripheral access had a lower PRISM score and PICU length of stay, 18 (SD: 8.5) and 9.5 (SD: 6.4) days vs. 8.9 (SD: 5.9) and 5.7 (SD: 3.6) days than patients with central access. The PIVC dwell time was 50.1 (SD: 65.3) hours and required 1.6 insertion attempts. Patients with three or more insertions had an increased odds ratio of 5.2 (95% CI: 3.1-8.5) to receive an extended dwell or midline insertion. Increased dwell time was associated with female gender, 42 hrs (P<.001), first attempt insertion, 53.5 hrs (P<.001), use of 24Ga bore, 56.3 hrs (P=.04), left-sided insertions, 54.9 (P=.07), less agitation, 54.8 hrs (P=.02), and less edema, 61.6 (P<.001). Decreased dwell time was associated with the use of Vancomycin infusion at 24.2 hrs (P<.001) and blood transfusions at 29.3 hrs (P<.001). CONCLUSIONS: Extended catheters last longer than PIVCs in the PICU. Deciding on extended catheter placement requires considering the length of treatment, and in addition, the overall body edema, the level of the patient’s restlessness, and the need for vancomycin infusion or blood transfusions since these factors diminish the dwell time of PIVCs and expose the patients to painful insertions. For such cases, an extended dwell catheter might be a better option even for shorter than six days of expected treatment.